Prevalence of hypertension in the urban population of Catanduva, in the State of São Paulo, Brazil - Freitas,Olavo de Carvalho (2001)
OBJECTIVE: To study the prevalence of systemic hypertension and its control in the population of Catanduva, in the state of São Paulo, Brazil. METHODS: We carried out a randomized cross-sectional population-based study of the urban population of Catanduva with individuals above 18 years of age (688 individuals accounting for 0.9% of the referred population). We interviewed study participants to analyze the major qualitative and quantitative variables that could influence the hypertensive scenario and the risk for systemic hypertension. Blood pressure was measured through the indirect method according to the III Consenso Brasileiro de Hipertensão (III Brazilian Consensus on Hypertension), which established blood pressure levels > or = 140/90 mm Hg as hypertensive. RESULTS: The prevalence of systemic hypertension was higher in individuals with: (1) history of hypertension (p<0.0001); (2) diabetes mellitus (p=0.05); (3) body mass index (B. M. I) > or = 25 kg/m² (p<0.001); (4) low educational level (p<0.0001); (5) familial income ranging from 1 to 5 minimum wages (p<0.05); (6) unmarried status (divorced/separated and widow(er)s) (p<0.0001). Of the interviewed individuals, 27.6% (p=0.05) had blood pressure levels under control. CONCLUSION: Our study showed that the prevalence of systemic hypertension was 31.5%, and that 27.6% of the individuals interviewed had blood pressure levels under control at the time of the interview.